Perspektif Dan Minat Mahasiswa Akuntansi Gen Z Terhadap Profesi Akuntan Publik - Devi Maya Sofa (AKUNTANSI 45, 2025)
This research aims to analyse the perspectives and interests of Generation Z accounting students towards the public accounting profession. The gap between the number of accounting graduates and the number of certified public accountants is a concern, while digital transformation is changing the nature of public accountants' work. Using qualitative methods with an interpretive approach, the research involved 21 students through Focus Group Discussions and in-depth interviews with 6 students at various levels of study. The results showed a significant development of perceptions as the study progresses; early level students tend to have views based on stereotypes with external factors (salary, status) as the main consideration, mid-level students develop a more complex understanding with the dominance of internal factors (intellectual challenges), while final level students show an integrated perspective with long-term considerations. Digital transformation is seen as an opportunity to reposition the role of public accountants to be more strategic and value-added, especially by middle and final year students. The research recommends curriculum development responsive to digital transformation, recruitment strategies that consider the characteristics of Generation Z, and simplification of professional certification pathways.